Tailoring the Overclaiming Technique to Capture Faking Behaviour in Applied Settings: A Field Study of Firefighter Applicants - Dunlop, P.; McNeill, I.; Jorritsma, Karina (ROUTLEDGE JOURNALS, TAYLOR & FRANCIS LTD, 2016)
In this study, we investigate the Overclaiming Questionnaire (OCQ) as a means of identifying faking behaviour in a sample of firefighter applicants. The OCQ asks respondents to report their knowledge of a set of items, some of which are fake (i.e., non-existent) items; thus claims of knowledge of these items cannot be legitimate. In this study, we developed a ’Fire-fighting OCQ’ with knowledge items that are relevant to firefighting. 519 firefighter applicants completed the Firefighting OCQ and a personality questionnaire, both of which were assessments to be considered for their potential selection into the role. Analyses revealed that overclaiming of knowledge on the Firefighting OCQ was positively associated with scores on a socially desirable responding scale as well as a ’faking’ factor extracted from the personality assessment. It appears that contextually relevant OCQs may be useful for identifying faking behaviour in operational selection settings.